Controlling liquid–liquid phase separation of G-quadruplex-forming RNAs in a sequence-specific manner. Issue 93 (2nd November 2022) - Tsuruta, Mitsuki; Torii, Takeru; Kohata, Kazuki; Kawauchi, Keiko; Tateishi-Karimata, Hisae; Sugimoto, Naoki; Miyoshi, Daisuke
Abstract : We constructed a minimum liquid–liquid phase separation model system using only G-quadruplex-forming oligonucleotides and cationic oligopeptides. Moreover, droplet redissolution was achieved in a sequence-specific manner. Abstract : We constructed a minimum liquid–liquid phase separation model system to form liquid droplets using only G-quadruplex-forming oligonucleotides and R- and G-rich oligopeptides. We found that the G-quadruplex structure is an essential component for RNA to form droplets with the peptide. Based on this model system and our findings, droplet redissolution via structure transition from a G-quadruplex to a duplex was achieved in a sequence-specific manner.